ANALYSIS ON THE SOURCE AND USAGE OF WORKING CAPITAL (A STUDY IN PT. JAPFA COMFEED INDONESIA, TBK IN THE PERIOD OF 2012-2016) - SATIFA, ARIZA PUTRI (Jurnal Ilmiah Mahasiswa FEB, 2018)
A very competitive economic development has a great impact on industrial sectors, especially in manufacturing industry. Good financial management and sound analysis on working capital sources and usage are necessary to create a healthy and growing company. This study aims to determine the source and usage of working capital in PT. Japfa Comfeed Indonesia, Tbk.. a manufacturing company engaged in the sector of basic industry in the sub- sector of animal feed.The data of this quantitative descriptive research is quantitative data in the form of the companyâ€™s financial statements from 2012 to 2016. The analysis uses reports of the capital changes and reports of working capital sources and usage.The results show that the working capital of the company during 2012-2016 tends to increase because its current assets, cash, and cash equivalents were increasing. Thesource and usage of working capital also tends to increase during 2012-2016 because the company experienced an increase in its internal working capital sources.Â Keywords: Working Capital, Source and Usage of Working Capital.